Cross-modal Transfer of Valence or Arousal from Music to Word Targets in Affective Priming?. Issue 3 (2nd October 2022) - Armitage, James; Eerola, Tuomas
ABSTRACT: This registered report considers how emotion induced in an auditory modality (music) can influence affective evaluations of visual stimuli (words). Specifically, it seeks to determine which emotional dimension is transferred across modalities – valence or arousal – or whether the transferred dimension depends on the focus of attention (feature-specific attention allocation). Two experiments were carried out. The first was an affective priming paradigm that will allow for the orthogonal manipulation of valence and arousal in both the words and music, alongside a manipulation to direct participants' attention to either the valence or the arousal dimension. Secondly, a lexical decision task allowed cross-modal transfer of valence and arousal to be probed without the focus of participants' attention being manipulated. Congruence effects were present in the affective priming task – valence was transferred in both the valence and arousal tasks, whereas arousal was transferred in the arousal task only. Contrary to predictions, the lexical decision task did not exhibit any congruence effects.